An Act to Organize, Discipline, and Govern the Militia of This Territory, Ch. 96, Sec. 11, in Revised Statutes of the Territory of Iowa (Reprint 1911). - (:unkn) unknown (My University, 1839)
That it shall be the duty of every non-commissioned officer and private, who owns a rifle, musket, or firelock, to appear with it in good order at every parade.
Keywords: ARMED FORCES